Pravo in ekonomija: Digitalno gospodarstvo (University of Maribor Press, 2020)
Law and Economics: Digital Economy. The publication in interdisciplinary and connected to the modern aspects of digitisation. It encompasses various contents with digitisation as its core topic, like: problem of exposure of Slovenia to the process of digitization and automation; digital advertisement and its impact of dental medicine tourism; digivino as a digital strategy and online tool for more efficient wine sales; problems with the effects of the must-carry rule on the enforcement of the right of cable retransmission when broadcasting RTV programs of special importance; blockchain technology and its impact on the conclusion of smart contracts; microtransactions and gambling; the question of responsibility for the conducts attributed to the artificial intelligence; advanced technologies and their impact on law and legal practice; and impact of uncertainty and systemic stress on Amazon share value. The publication gives answers to several legal and economic as well as other questions concerning digitisation and the use of advanced technologies in the fields which are the subject matter of this publication.